The Kitchen God's Wife - Amy Tan (USA Ivy Books, 1992)
Winnie and Helen have kept each other's worst secrets for more than fifty years. Now, because she believes she is dying, Helen wants to expose everything. And Winnie angrily determines that she must be the one to tell her daughter, Pearl, about the past--including the terrible truth even Helen does not know. And so begins Winnie's story of her life on a small island outside Shanghai in the 1920s, and other places in China during World War II, and traces the happy and desperate events that led to Winnie's coming to America in 1949.
Originally published: New York : Putnam, c1991.
Keywords: Chinese fiction; Families -- Fiction; Domestic fiction; General